Optimal design of distribution system using Artificial Immune System (AIS) technique / Muhammad Ridzuan Badli - Badli, Muhammad Ridzuan (2008)
This paper presents optimal design of distribution system by using Artificial Immune System (AIS) technique. The main is to evaluate optimal cost of distribution substation an also loads objective distance connected to substation. By selecting the best of an initial set of control variables from the beginning of the optimization procedure, this method can be worked out excellently to achieve the main objective function to minimize instantaneous costs. The Artificial Immune System (AIS) were written in MATLAB. Test was conducted on the 16-bus system.